Molecular mechanisms of regulation of erythropoiesis and stress erythropoiesis - Momčilović Sanja; Bogdanović Andrija; Vignjević-Petrinović Sanja (Medicinski Podmladak)
Erythropoiesis under basal conditions involves the continuous production of new erythrocytes at a constant rate. During the adult period, erythropoiesis takes place primarily in the bone marrow and has a substantial capacity. The regulation of this process is achieved through a multitude of cellular and molecular mechanisms that synergistically act to ensure adequate tissue oxygenation while avoiding viscosity-related issues associated with excessive production. Therefore, this process is regulated through both positive and negative feedback mechanisms. In contrast to the continuous renewal of erythrocytes under basal conditions, disruptions in homeostasis such as bleeding, stress, inflammation, etc., lead to the activation of a process known as stress erythropoiesis. Stress erythropoiesis is a unique process that, in addition to the bone marrow, also occurs extramedullary. Extramedullary erythropoiesis primarily takes place in the red pulp of the spleen, where, under the influence of specific signals within its microenvironment, there is an extensive expansion of immature erythroid cell populations. This process ensures an adequate response to the increased demands for erythropoiesis. This paper elucidates the fundamental molecular mechanisms involved in regulating erythropoiesis under basal conditions and stress erythropoiesis. It highlights the dependency of these molecular mechanisms on the microenvironment in which these processes occur. Understanding the molecular mechanisms that govern erythropoiesis and stress erythropoiesis is crucial for advancing therapeutic strategies for hematological disorders.